Prevalence of new psychoactive substances addiction: a hospital-based cross-sectional study - Mariya Prilutskaya; Oleg Yussopov; Nikolay Negay; Kuanysh Altynbekov; Makpal Tokayeva (National Scientific Medical Center, 2020)
Background: New psychoactive substances are a combined group of chemical substances developed in an attempt to circumvent control and restrictive measures for traditional drugs. Until 2017, the countries of Central Asia remained a gray spot on the maps of epidemiological new psychoactive substances reports. The largest share of new psychoactive substances on the Kazakhstani market became of a serious concern for both the law enforcement authorities and the public health services during the last five years. Objectives: The aim of the study was to assess the proportion of hospitalizations in Kazakhstan related to new psychoactive substances addiction over a three-year period (2016-2018) and to describe the patterns of new psychoactive substances use in the sample of admitted patients. Material and methods: This study was a retrospective, cross-sectional investigation using regional databases consisting of the 2018 cases of hospitalizations at 16 state regional mental treatment centers and 3 state narcological clinics across Kazakhstan. We analyzed 345 cases of NPS addiction. Results: The proportion of admitted in 2018 new psychoactive substances patients amounted to 10.01% (9.1%; 11.1%), comprising an ascending trend since 2016. The highest prevalence of the new psychoactive substances addiction was registered in Nur-Sultan, Almaty cities, and North-Kazakhstan region. Cathinones prevailed over other NPS groups (71.9%) and were mostly used in parallel with traditional opioids. Synthetic cannabinoids (28.1%) were associated with herbal cannabis use in three quarters of cases; smoking absolutely prevailed as the main route of their administration. Conclusion: This study suggests that new psychoactive substances addiction is a current clinical phenomenon, which should be reflected in the development and revision of the national drug treatment programs across Kazakhstan. The disparity of new psychoactive substances prevalence in the regions should be considered in the development of local anti-drug plans by the health care service and law enforcement authorities.